Gingival Mesenchymal Stem Cells Metabolite Decreasing TRAP, NFATc1, and Sclerostin Expression in LPS-Associated Inflammatory Osteolysis In Vivo - Nugraha, Alexander Patera; Ramadhani, Nastiti Faradilla; Riawan, Wibi; Ihsan, Igo Syaiful; Ernawati, Diah Savitri; Ridwan, Rini Devijanti; Narmada, Ida Bagus; Saskianti, Tania; Rezkita, Fianza; Sarasati, Andari; Noor, Tengku Natasha Eleena Binti Tengku Ahmad; Inayatillah, Bilqis; Nugraha, Albertus Putera; Joestandari, Florentina (European Journal of Dentistry, 2022)
Objective Bone is a dynamic tissue that undergoes remodeling. During bone remodeling, there are transcription factors such as nuclear factor-activated T cells-1 (NFATc1), sclerostin, and tartrate-resistant acid phosphatase (TRAP) that are released for bone resorption. Metabolite from gingival mesenchymal stem cells (GMSCs) has the ability to activate proliferation, migration, immunomodulation, and tissue regeneration of bone cells and tissues. Furthermore, the aim of this study is to investigate the metabolite of GMSCs' effect on expression of NFATc1, TRAP, and sclerostin in calvaria bone resorption of Wistar rats.Materials and Methods Twenty male healthy Wistar rats (Rattus norvegicus), 1 to 2 months old, 250 to 300 g body were divided into four groups, namely group 1 (G1): 100 µg phosphate-buffered saline day 1 to 7; group 2 (G2): 100 μg lipopolysaccharide (LPS) day 1 to 7; group 3 (G3): 100 μg LPS + 100 μg GMSCs metabolite day 1 to 7; and group 4 (G4): 100 μg GMSCs metabolite day 1 to 7. Escherichia coli LPS was used to induce inflammatory osteolysis on the calvaria with subcutaneous injection. GMSCs metabolite was collected after passage 4 to 5, then injected subcutaneously on the calvaria. All samples were sacrificed on the day 8 through cervical dislocation. The expression of TRAP, NFATc1, and sclerostin of osteoclast in the calvaria was observed with 1,000× magnification.Statistical Analysis One-way analysis of variance and Tukey honest significant different were conducted to analyze differences between groups (p < 0.05).Results The administration of GMSCs metabolite can significantly decrease TRAP, NFATc1, and sclerostin expression (p < 0.05) in LPS-associated inflammatory osteolysis calvaria in Wistar rats (R. norvegicus). There were significantly different TRAP, NFATc1, and sclerostin expressions between groups (p < 0.05).Conclusion GMSCs metabolite decrease TRAP, NFATc1, and sclerostin expression in LPS-associated osteolysis calvaria in Wistar rats (R. norvegicus) as documented immunohistochemically.
Keywords: stem cells; lipopolysaccharide; medicine; infectious disease; dentistry